The relationship between the microclimate and the landscape design of theme park - Md. Johari, Norsyazwani (2014)
This study aims to help the development of the theme park through the understanding of the relationship between local climate and landscape design via the experiences and views from tourists which can be used as a medium to create the value of satisfaction and comfort during their visit to the theme park. Microclimate was defined as the local climate of one area in which to engage in any development or construction, knowledge and research on the climate of the area should be studied in advance so the developments can be aligned and considered with the local climate. Microclimate responds to every development in the surrounding including landscape construction. Design and use of the landscape plays an important role, especially for a theme park where the landscape use as a medium of intermediary in between of one area with local climate in order to help visitors adapt to local climate through landscape design. To produce the landscape design of theme park that considering the local climate, the understanding towards the tourist's experience and perspectives are very important. Therefore, a quantitative analysis study was conducted in a Legoland Malaysia theme park to study the typology of tourists, tourist's experience on the use of landscape, tourist's perspective on the overall landscape design with the local climate and lastly the overall assessment of the level of satisfaction of tourists during their stay in the theme park. The outcome of the research found some landscape design constraints towards the local climate has been identified and suggestions for future research were discussed and proposed. The understanding towards this study can help in creating a design that is more accurate and sensitive to the local climate in order to provide maximum comfort and satisfaction to the theme park's user, either domestic tourist or international tourists.